Teaching and learning data structure concepts via Visual Kinesthetic Pseudocode with the aid of a constructively aligned app. Issue 6 (20th September 2016) - Odisho, Ogen; Aziz, Mark; Giacaman, Nasser
Abstract: Data Structures is an integral topic for any Computer Science or Software Engineering degree, identified as a Core Tier‐1 topic of the ACM/IEEE Computer Science Curricula. The underlying concepts are inherently abstract, making them especially difficult to understand for novice programmers. This paper proposes a cognitively challenging technique to help students understand the thought process that the learning outcomes of fundamental data structure units aim to achieve. The development of this thought process is using a technique we term Visual Kinesthetic Pseudocode, with the overarching goal of helping students code without coding, yet providing the necessary scaffold to guide them in implementing the data structures with real code. This was implemented in the form of INTERACTIVE DS, an app for students and teachers to guide the learning of fundamental data structure concepts. The evaluations demonstrate that students strongly credited INTERACTIVE DS in aiding their understanding of concepts and confidence in applying data structure concepts in practice. The study is also a step forward in revealing potential threshold concepts pertaining to data structure modules. © 2016 Wiley Periodicals, Inc. Comput Appl Eng Educ 24:926–933, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21768